Desain dan Implementasi Mobile Learning Sebagai Upaya Peningkatan Pembelajaran Bahasa Arab di Madrasah Aliyah - Khotijah Khotijah; Ahmad Arifin (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2021)
This research aims to design and implement mobile learning using Google Classroom and Quizizz applications for Arabic subjects for Madrasah Aliyah (Islamic Senior High School) students. This research is how to design, develop, and implement mobile learning in Arabic subjects among Madrasah Aliyah students. This learning media is made so that users can easily access an Arabic subject matter. The research target to be achieved is the existence of different exciting and easy-to-use learning media to increase student interest in learning and achievement in Arabic subjects. The research method used is experimental research with the design of this research model is one group pretest-posttest design. This research was conducted from January-August 2020. The subject of this study was Arabic language learning conducted at MA Nurul Ulum, Kota Gajah, and MA Ma'arif 9, Kota Gajah. The results show that the development of android-based mobile learning still has not demonstrated results and effectiveness on learning outcomes but is effective in growing motivation and interest in learning Arabic.